The Celtic way of evangelism : how Christianity can reach the West-- again - Hunter, George G., 1938- (Nashville : Abingdon Press, 2010)
Celtic Christianity -- the form of Christian faith that flourished among the people of Ireland during the Middle Ages -- has gained a great deal of attention lately. George G. Hunter III points out that while the attention paid to the Celtic Christians is well deserved, much of it fails to recognize the true genius of this ancient form of Christianity. What many contemporary Christians do not realize is that Celtic Christianity was one of the most successfully evangelistic branches of the church in history. The Celtic church converted Ireland from paganism to Christianity in a remarkably short period, and then proceeded to send missionaries throughout Europe. North America is today in the same situation as the environment in which the early Celtic preachers found their mission fields: unfamiliar with the Christian message, yet spiritually seeking and open to a vibrant new faith. If we are to spread the gospel in this culture of secular seekers, we would do well to learn from the Celts. Their ability to work with the beliefs of those they evangelized, to adapt worship and church life to the indigenous patterns they encountered, remains unparalleled in Christian history. If we are to succeed in reaching the West . . . again, then we must begin by learning from these powerful witnesses to the saving love of Jesus Christ.
The Gospel to the Irish -- A new kind of community, a new kind of life -- To the Picts, the Anglo-Saxons, and other "barbarians" -- The Celtic Christian community in formation and mission -- How Celtic Christianity communicated the Gospel -- The missionary perspective of Celtic Christianity -- The relevance of first-millennium Celtic Christianity for third-millennium Western Christianity -- The Celtic future of the Christian movement in the West.
Includes bibliographical references and index.
Keywords: Celtic Church; Evangelistic work -- Western countries